PENDAMPINGAN DAN PENGEMBANGAN LITERASI UNTUK SUPORTER SEPAKBOLA MELALUI JURNALISME SEPAKBOLA - Fajar Junaedi; Filosa Gita Sukmono (WARTA LPM, 2019)
Football and journalism are two domains that are closely interrelated. Football sports news developed in various media platform, such as printed, electronic and online media. Football supporters, in general, are active audiences who are intensely consuming sports news. In the context of media literacy, the existence of football supporters as an active audience is a potential for the development of media literacy. The media literacy that be developed in this program is media literacy in the process of media production, namely football journalism writing. Football supporters generally come from young people who have the potential to increase their competence in terms of football journalism, but they have lack access for developing their competence. The solution is to provide assistance and development of media literacy through football journalism activities. This service activity involves Indonesian Fandom as a partner. Activities carried out in this community service program are training, workshops and mentoring for writing football journalism. There were twenty-five participants who participated in this activity. The results of the activity in the form of articles, which in general the theme is about local football, edited by partners. Articles that have been edited are then compiled into one text book entitled Merawat Sepakbola Indonesia (Caring for Indonesian Football). The book was successfully printed as many as two hundred copies, and sold through networks owned by partners, and involved workshop participants as resellers. Thus, this program has succeeded in increasing football literacy among supporters, and fostering entrepreneurial networks of supporters through the publishing and distribution of book sales.